Determinants of exclusive breastfeeding among Haitian children under 6 months of age - Stéphane Decelles; Milena Nardocci; Alison Mildon; Bana Salameh; Malek Batal (Pan American Health Organization, 2022)
Objective. To identify the determinants of exclusive breastfeeding (EBF) among children under 6 months of age from three regions in the South and GrandAnse Departments of Haiti. Methods. Data were pooled from three cross-sectional surveys conducted yearly from 2017 to 2019 with the guardians of 638 children under 6 months of age. A non-quantitative 24-hour dietary recall was used to assess EBF the day before the survey. Using unadjusted and adjusted prevalence ratios, associations were assessed between EBF and several explanatory factors: infants age and sex; maternal age, educational attainment, mid-upper arm circumference (MUAC), dietary diversity, number of children under 5 years of age, responsibility for the main or secondary source of income of the household, initiation of breastfeeding within one hour, knowledge of EBF duration; household severe food insecurity, socioeconomic status, dependency ratio, region, and residential zone (urban/rural). Results. Prevalence of EBF was 68% in the study sample. From the fully adjusted model, prevalence of EBF was statistically significantly higher among younger infants, mothers with larger MUAC, who met or exceeded Minimum Dietary Diversity for Women (MDD-W), who initiated breastfeeding within one hour, who were knowledgeable of the recommendations for EBF duration, and living in the Jérémie region. Conclusions. The main determinants of EBF identified in this study attest to the importance of breastfeeding mothers access to nutritious food for the practice and maintenance of EBF and the need for geographically equitable access to health services and education that support breastfeeding.